Academic Folklore Research in Canada: Trends and Prospects (Part 1) - Pocius, Gerald (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2000)
This is a report written for the Department of Canadian Heritage on the state of academic folklore research in Canada. Written in 1998, the study addresses how Canada has followed the UNESCO declaration of 1989 regarding the Safeguarding of Traditional Culture and Folklore. This essay will be published in two parts. This first section deals with the initial three parts of the UNESCO Declaration: definition of folklore; identification of folklore; conservation of folklore (which includes collecting and professional training). Folklore has been defined within Canada along language, ethnic or regional fines. Folklore has been identified using catalogues and indexes from the United States and France, although Canadian guides have been developed. The conservation of folklore has taken place at archives (such as at Laval and Memorial) and at museums (such as the Canadian Museum of Civilization). Little systematic collecting has occurred across the country. The largest centres for professional folklore training are at Laval and Memorial.